The revival of urban social and neighbourhood movements in Spain: a geographical characterization - Lois-González, Rubén C.; Piñeira-Mantiñán, Maria José (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
The current economic and financial crisis manifests itself specifically in cities and metropolitan areas. As in other periods of recession throughout history, one of the characteristic features of this crisis was the bursting of a housing bubble. In Spain, the spectacular construction boom slowed down, and many families could not afford to pay the mortgages on their main or second homes. At the same time, welfare spending was slashed to meet the obligations of the banks and cajas (savings banks) ruined by the property slump. In addition, the unemployment rate rose to above 20 %. As a result of this process, urban space reflects the resurgence of social and political movements of different kinds, ranging from more defensive movements focused on a particular place (against the closure of a company or an eviction order issued to a mortgage victim) to more general movements demanding direct democracy and an end to corruption. These movements fuelled the indignados protest with its camps on the streets of all major cities. This article primarily aims to classify urban social movements in contemporary Spain on the basis of their motives and demands. Secondly, it proposes a presentation of the movements assessing their impact on cities and their preferred demonstration spaces inside the city. Finally, it analyses their political-urban character in relation to local resistance, e.g. in Burgos, demands for urban communal ownership, the occupation of squares and houses, and the focus on creating new political expressions such as mareas ciudadanas (citizen tides) and the Podemos phenomenon.